Reasons and Patterns of Permanent Teeth Loss among Patients attending a Dental College in Kathmandu - Khapung, Anju; Rao, G. Nagaraja; Shrestha, Sujita (Journal of Nepalese Society of Periodontology and Oral Implantology, 2020)
Introduction: According to World Health Organization, oral health means the retention throughout life of a functional, aesthetic and natural dentition of not less than 20 teeth and not requiring a prosthesis. The major reasons for tooth loss are dental caries and periodontal disease. Proper understanding of reasons for tooth loss helps to improve oral health. Objective: To identify the reasons and patterns of permanent teeth loss among patients attending Kantipur Dental College. Methods: A cross-sectional study was carried out among 403 patients aged 18 years and above attending Kantipur Dental College, Kathmandu by convenience sampling method. Data was collected through structured questionnaire and clinical examination and was analysed using SPSS version 20. Results: A total of 403 patients were examined of which 38% had tooth loss. Mean number of tooth loss was 2.99+3.44. Statistically significant difference was found in mean tooth loss between age groups and levels of education (P value < 0.001). Dental caries was the most common reason of tooth loss followed by periodontal disease. Most common reason for not saving the tooth was "tooth cannot be saved" (65.1%). Mandibular molars accounted for majority of tooth loss followed by maxillary molars. Conclusion: The results of the present study show that dental caries was the major cause of tooth loss irrespective of the age group. It points out the need to carry out oral health awareness and other preventive programs both at school and community levels.